Identifikasi Batita Berpotensi Stunting di Dusun Mertelu Kulon Kalurahan Mertelu Kapanewon Gedangsari Kabupaten Gunungkidul - Rosalia Widhiastuti Sri Lestari; Afriyanti Afriyanti; Suindartini Suindartini (Pancanaka, 2022)
Stunting is condition where toddler experience abnormal growth. Many elements cause toddler born with stunting condition, start from candidate manten who doesn't guard health, home and environment, water source used every day, intake nutrition, pattern nurturing, and knowledge about child growth. This study use qualitative approach. Locus research in Kapanewon Gendangsari. Object study this are 10 toddlers who have the potential for stunting. These toddlers were chosen as the object of research because they reffered to quantitative data released by the Gunungkidul District Health office in 2021. Data collection techniques were interviews. The data processing technique use d is qualitative data analysis including: data collection, data reduction, data presentation, and verification and coclusions. There are several toddlers who are concluded to have the potential for stunting based on the indicators set by the government. At their age, the toddlers have a height below the standard set by the Regulation of The Minister of Health of the Republic of Indonesian. The reasons why the toddlers are at risk of stunting is inferred because of lack of literacy of understanding of stunting, its causes, and how to prevent it.